Galleria mellonella as an experimental model to study human oral pathogens - Rossoni, Rodnei Dennis [UNESP]; Ribeiro, Felipe de Camargo [UNESP]; dos Santos, Hanna Flávia Santana [UNESP]; dos Santos, Jéssica Diane [UNESP]; Oliveira, Nicássia de Sousa [UNESP]; Dutra, Marignês Theotonio dos Santos [UNESP]; de Lapena, Simone Aparecida Biazzi [UNESP]; Junqueira, Juliana Campos [UNESP] (Elsevier, 2019)
The oral cavity is home to a microbial community of more than 800 species. This important microbiome is formed by commensal and opportunistic bacteria, fungi and viruses. Several distinct habitats within the mouth support heterogeneous microbial communities that constitute an important link between oral and general health. The use of animal models for in vivo studies in microbial pathogenicity is well established in the scientific community. Galleria mellonella as a model host has increased in use significantly in the last few years. This invertebrate model provides studies on a large scale, serving as screens for studies on vertebrate animals, such as mice and rats. In this review, different studies of microbial genera of dental importance (Enterococcus, Candida, Lactobacillus, Porphyromonas and Streptococcus) are discussed, highlighting the use of G. mellonella as a suitable model for studying pathogenesis, efficacy of antimicrobial compounds, and immune responses.
Keywords: Experimental model; Galleria mellonella; Oral pathogens; Pathogenesis